2005
DOI: 10.1074/jbc.m407749200
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid Uptake by Cultured Cells

Abstract: Human fibroblasts, rat neurons, and murine neuroblastoma cells, cultured in the presence of fetal calf serum, were fed with [1-3 H]sphingosine to radiolabel sphingolipids. The fate of cell sphingolipids, the release of sphingolipids in the culture medium, the interaction of sphingolipids with the proteins and lipoproteins of fetal calf serum, and the fate of sphingolipids taken up by the cells were investigated. For this latter purpose, the culture medium containing radioactive sphingolipids was delivered to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…The effects of bSMase on ERM proteins reported previously by our group (20) could be exerted by the effect of bSMase on cellular SM or on the SM associated with lipoproteins found in FBS. We observed that FBS used in cell culture is rich in SM, consistent with previous studies (35). Thus, bSMase treatment of FBS medium caused hydrolysis of SM not only in the cells but also in the medium.…”
Section: Resultssupporting
confidence: 80%
“…The effects of bSMase on ERM proteins reported previously by our group (20) could be exerted by the effect of bSMase on cellular SM or on the SM associated with lipoproteins found in FBS. We observed that FBS used in cell culture is rich in SM, consistent with previous studies (35). Thus, bSMase treatment of FBS medium caused hydrolysis of SM not only in the cells but also in the medium.…”
Section: Resultssupporting
confidence: 80%
“…The acyl chains of ether-linked lipids and the N-linked acyl chains for sphingomyelin (SM), ceramide (Cer) and glycosphingolipids (GSLs) are shown after the slash. All samples, including the controls were cultured in the presence of the same amount of media and FCS and we assume that the small amount of FCS in the culture media is not affecting the cellular lipid metabolism [18].…”
Section: Methodsmentioning
confidence: 99%
“…(484) Hydrolytic enzymes for sphingolipids are also found in other locations in the cell to produce bioactive products for cell signaling 5,6 and rearrangement of membrane architecture. 23,485 The complete balance sheet for sphingolipids additionally includes uptake of sphingolipids from exogenous sources (such as albumin and lipoproteins) 486,487 and losses by efflux,(488) lipoprotein secretion, 354,489 and shedding of membrane vesicles containing sphingolipids. (490)…”
Section: Sphingolipid Metabolic Pathwaysmentioning
confidence: 99%